THE EFFECT OF TERMS OF TRADE SHOCKS ON AGRICULTURAL PRODUCT IN IRAQ FOR THE PERIOD (1990 – 2022) - Raja T. Al-Wasity; Hala A. Al-Attabi; Saad A. Al-Badawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This research was aimed to study and analyze the impact of the shocks of the agricultural net terms of trade (NBTT) on agricultural product (AP) in Iraq during the period (1990 – 2021), which are among the shocks affecting the agricultural sector and foreign trade, the research used quantitative approaches in estimating the levels of impact, including VAR model, variance decomposition analysis (VDA) and impulse response function (IRF). The results showed that VDA of AP was weak in respect of agricultural NBTT and vice versa. While IRF of NBTT was negative in respect of Ap, and the same result was for IRF of AP. The study recommended the need to consider strategies to support smallholder farmers, such as providing access to credit, soft loans, technical assistance and markets for their products, in addition of support the technological advancements for their role in shaping the relationship between agricultural trade and agricultural production.